Changes in conceptions in women younger than 18 years and the circumstances of young mothers in England in 2000–12: an observational study. Issue 10044 (6th August 2016) - Wellings, Kaye; Palmer, Melissa J; Geary, Rebecca S; Gibson, Lorna J; Copas, Andrew; Datta, Jessica; Glasier, Anna; Scott, Rachel H; Mercer, Catherine H; Erens, Bob; Macdowall, Wendy; French, Rebecca S; et al.
Summary: Background: In 2000, a 10-year Teenage Pregnancy Strategy was launched in England to reduce conceptions in women younger than 18 years and social exclusion in young parents. We used routinely collected data and data from Britain's National Surveys of Sexual Attitudes and Lifestyles (Natsal) to examine progress towards these goals. Methods: In this observational study, we used random-effects meta-regression to analyse the change in conception rates from 1994–98 to 2009–13 by top-tier local authorities in England, in relation to Teenage Pregnancy Strategy-related expenditure per head, socioeconomic deprivation, and region. Data from similar probability sample surveys: Natsal-1 (1990–91), Natsal-2 (1999–2001), and Natsal-3 (2010–12) were used to assess the prevalence of risk factors and their association with conception in women younger than 18 years in women aged 18–24 years; and the prevalence of participation in education, work, and training in young mothers. Findings: Conception rates in women younger than 18 years declined steadily from their peak in 1996–98 and more rapidly from 2007 onwards. More deprived areas and those receiving greater Teenage Pregnancy Strategy-related investment had higher rates of conception in 1994–98 and had greater declines to 2009–13. Regression analyses assessing the association between Teenage Pregnancy Strategy funding and decline in conception rates in women younger than 18 years showed an estimated reduction in the conception rate of 11·4 conceptions (95% CI 9·6–13·2; p<0·0001) per 1000 women aged 15–17 years for every £100 Teenage Pregnancy Strategy spend per head and a reduction of 8·2 conceptions (5·8–10·5; p<0·0001) after adjustment for socioeconomic deprivation and region. The association between conception in women younger than 18 years and lower socioeconomic status weakened slightly between Natsal-2 and Natsal-3. The prevalence of participation in education, work, or training among young women with a child conceived before age 18 years was low, but the odds of them doing so doubled between Natsal-2 and Natsal-3 (odds ratio 1·99, 95% CI 0·99–4·00). Interpretation: A sustained, multifaceted policy intervention involving health and education agencies, alongside other social and educational changes, has probably contributed to a substantial and accelerating decline in conceptions in women younger than 18 years in England since the late 1990s. Funding: Medical Research Council, Wellcome Trust, Economic and Social Research Council, and Department of Health.